2012
DOI: 10.1371/journal.pone.0032640
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence and Age at Diagnosis among Children with Type 1 Diabetes Mellitus over a 20-Year Period in Auckland (New Zealand)

Abstract: BackgroundWe aimed to evaluate the incidence of type 1 diabetes mellitus in children <15 years of age (yr) in the Auckland region (New Zealand) over 20 years (1990–2009).MethodsWe performed a retrospective review of all patients <15 yr diagnosed with type 1 diabetes, from an unselected complete regional cohort.ResultsThere were 884 new cases of type 1 diabetes, and age at diagnosis rose from 7.6 yr in 1990/1 to 8.9 yr in 2008/9 (r2 = 0.31, p = 0.009). There was a progressive increase in type 1 diabetes inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 19 publications
7
53
0
Order By: Relevance
“…The UE-IR of T1DM girls was higher than that of boys over a period of 16 years, which is consistent with our findings in the period of 1988-1996 [5] and international research data [15,16]. Some studies found no differences between genders [17,18,19] or the incidence in boys was higher than that in girls [20,21]. A high incidence in diabetes in girls may be one of the features of T1DM in China.…”
Section: Discussionsupporting
confidence: 92%
“…The UE-IR of T1DM girls was higher than that of boys over a period of 16 years, which is consistent with our findings in the period of 1988-1996 [5] and international research data [15,16]. Some studies found no differences between genders [17,18,19] or the incidence in boys was higher than that in girls [20,21]. A high incidence in diabetes in girls may be one of the features of T1DM in China.…”
Section: Discussionsupporting
confidence: 92%
“…T1DM accounts for about 5-10 % of all cases of diabetes, and its incidence seems to be increasing worldwide [18][19][20][21]. It results from an autoimmune destruction of insulin-producing beta cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) has become a hot research point because of its increasing incidence worldwide [1]. T1DM is an organ-specific disorder characterized by the autoimmune destruction of the β cells of pancreatic islets.…”
Section: Introductionmentioning
confidence: 99%